Uterine rupture in nulliparous woman without risk factors: a case report and literature review - Seca, Marta Seca; Selvaggia, Bettoni Gaya Selvaggia; Paola, Fenili Paola; Francesco, Clemente Francesco; Patrizia , D’Oria Patrizia; Paola, Algeri Paola (BOHR Journal of Obstetrics and Gynaecology, 2023)
Objective: The aim of this study was to summarize the main features of spontaneous uterine rupture in primigravid patients before the onset of labor, emphasize the possibilities of therapeutic conduct, and offer points of reflection on the post-rupture management. Methods: We performed a literature review of all the individual case reports, retrospective case series, and reviews concerning uterine rupture in peer-reviewed journals from January 1975 to October 2021. Results: The diagnosis of uterine rupture was commonly made by abdominal pain, with or without concomitant nausea and vomiting. Uterine ruptures occur more frequently at the end of pregnancy or in the third trimester. The most frequently involved site is the uterine cornua followed by the posterior wall of the uterus. Other described cases identify the broad ligament, uterus sacral ligament, lower uterine segment, and anterior wall as possible points of rupture. The most frequently used suturing technique is the repair of the breach in two layers. Conclusion: Uterine rupture is an extremely rare obstetric emergency, correlated to life-threatening consequences for both the newborn and the woman. Considering the maternal and fetal risks, a tempestive diagnosis is mandatory. .